Combating the global environmental crisis using indigenous ecological knowledge: the case of Kwahu traditional area, Ghana - Asante, Daniel Boamah; Adom, Dickson; Asante, Afua; Gyamera, Vera (Frontiers in Human Dynamics, 2025)
This study explores Indigenous ecological knowledge from the Kwahu Traditional Area in Ghana as a compelling case study amid an escalating global environmental crisis. It reassesses traditional environmental conservation, emphasizing the intricate practices that sustain the Kwahu people’s harmonious relationship with their natural environment. The study focuses on the Kwahu people’s indigenous methods of environmental regulation, including their reverence for totemic animals, traditional understanding of land and water bodies, and observance of sacred or taboo days. The findings demonstrate that the Kwahu people’s reverence for totemic creatures acts as ecological custodians, reflecting the interconnectedness of human and non-human realms. Moreover, the study reveals the Kwahu’s unique and holistic understanding of land and water bodies, showing how these perceptions contribute to sustainable land use and resource management, enhancing ecological resilience. Additionally, observance of sacred or taboo days is crucial to the Kwahu’s Indigenous environmental management, blending nature’s spiritual and ecological aspects. These designated days provide periods of rest for the natural world and illustrate the deep respect the Kwahu people have for nature. By examining and illuminating these Indigenous conservation practices, the study emphasizes their ongoing relevance amid urgent global environmental challenges. The study offers valuable insights into how Indigenous ecological knowledge systems can inform and complement contemporary environmental conservation efforts, presenting a holistic and culturally rooted approach to addressing the complex environmental crises facing our planet. In this regard, Indigenous ecological practices often incorporate ecological, cultural, social, and spiritual components, which provide a holistic understanding of ecosystems. This perspective is crucial for enhancing modern conservation efforts as it recognizes the interconnectedness of humans and nature.